Precarization of Working Class Roma through Spatial Deprivation, Labor Destitution and Racialization (Szociológiai Szemle, 2023)
This article addresses the topic of the current issue of the journal (processes of poverty and social exclusion) by (re)framing the working class position of dispossessed Roma through a case study conducted in Romanian localities. The situation of the Roma is due to the fact that they stand at an intersection: the product of a combination of their precarious spatial position, the nature of the labor that they have access to and the racialization of both poverty and Roma ethnicity. Moreover, this position is shaped by the relationship of the Roma to capital; the Roma being the group most adversely affected by de-industrialization, deregulation of the labor and housing market, and through the re-regulation of property relationships; in particular real estate goods. The latter processes produce poverty and social exclusion, among other things, because they increase the unevenness of development across regions, counties, localities and within settlements, and lead to the creation of insecure and underpaid jobs or structural unemployment. Dispossessed of the means of production, and also of (state) support for adequate housing (one of the resources for the social reproduction of the labor force), the impoverished Roma take up poorly paid formal employment or engage in insecure informal labor either domestically or abroad; a phenomenon that aggravates their exploitation as a working class undergoing a severe process of precarization. The analysis in this paper is based on the empirical results of qualitative research conducted between 2012-2014 in several localities in Romania under the umbrella of the contextual inquiry Faces and Causes of Marginalization of the Roma in Local Settings. Going beyond the initial theoretical frame of that research, which addressed the role of ethnic relations to other factors which affect the inclusion/exclusion of the Roma, this article responds to the need to better understand these processes in terms of how the system adversely impacts dispossessed Roma via their exploitation as workers whose precarization is a result of their position at the crossroads of spatial deprivation, labor-related destitution and racialization. In this endeavor, the article relies on the conclusions of another investigation that understands the socio-territorial exclusion of dispossessed Roma as form of racialized class exploitation.